Age of callus tissues and cotyledonary materials on the selection of cocoa swollen shoot virus-free somatic embryos - Quainoo, A. K. (Research in Biotechnology, 2011)
Research was conducted to investigate the effect of age of callus tissue and cotyledonary material on the selection of CSSV-free cocoa somatic embryos. Polymerase chain reaction (PCR) capillary electrophoresis was more sensitive and quick in detecting the CSSV than PCR/agarose electrophoresis. PCR/capillary electrophoresis revealed the presence of CSSV in callus tissues in 1wk at the rate of 53(82 %), 47(94 %) and 46(85 %) for three infected Amelonado cocoa trees, T1, T2 and T4, respectively whileÃ‚Â PCR/agarose electrophoresis recorded 23(36 %), 19(38 %) and 26(48 %) for T1, T2 and T4), respectively.